(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
Sorghum is a key crop in Kenya’s attainment of food and nutrition security. Climate is a key determinant of sorghum production under rainfed conditions. The overall objective of this study was to examine variations of sorghum yields in response to climate. This is crucial in documenting future strategic options to enhance food security in a changing climate. A longitudinal research design was used in the study. Purposive and cluster sampling techniques were used to select sorghum and climate data from lower eastern Kenya’s districts covering the period 1979-2009. Association between sorghum crop yields and climate data were sought through correlation analysis, while variability in yields was determined through the coefficient of variation (CVs) and standard deviations (STDEV). There wide sorghum yield and climate variability with high CV values of up 60 % of rainfall. Kitui had the lowest variation in sorghum yields with a Standard deviation of 344.1 Kg/Ha (CV = 38.7 %) while Machakos had the highest variation with STDEV of 591.6 Kg/Ha (CV = 60.5 %). This information is useful to monitor and forecast future sorghum production under rain-fed agriculture. There is a need to continue with focused applied research to unleash sorghum’s capacity to be the cornerstone of food security in Kenya.